The prehistory of innovation: A longer view of penal change - Rubin, Ashley T. (Punishment & society, 2018)
New penal technologies, however innovative, rarely emerge fully formed, but we currently lack a theoretical appreciation of the lengthy, messy process by which penal innovations develop. Indeed, most studies of penal change focus on the conditions surrounding the emergence of a particularly successful innovation, a model of punishment whose widespread diffusion is indicative of significant change. This paper extends our analytical focus by examining the legacy of an innovation’s prehistory, the ideational period in which an idea is created at the margins of criminal justice before manifesting on a wider scale. This paper traces the history, and influence, of American uses of penal incarceration before Pennsylvania’s famous Walnut Street Prison, often referred to as the country’s first prison. This prehistory complicates the notion of innovation by identifying significant precursors. Ultimately, recognizing penal innovations’ prehistory challenges macro-level theories of penal change, which largely overlook those causes that significantly predate the “moment” of innovation.